PERSEPSI WISATAWAN DALAM IMPLEMENTASI SAPTA PESONA DI OBJEK WISATA BELERANG SIMPUR DESA KECAPI - Naudita Novita Sari; Gunardi Djoko Winarno; Sugeng Prayitno Harianto; Yulia Rahma Fitriana (Forestry Study Program University Of Mataram, 2020)
The perception of tourists is a source of information and evaluation for managers of the concept of sapta pesona that has been applied to attractions. The importance of the role of tourist can influence the management of sustainable ecotourism. This study aims to analyze the potential of tourist attractions and tourist perceptions of the implementation of sapta pesona. Determination of the sample is done by using purposive sampling. Data were collected by interview and observation techniques in the field, then analyzed descriptively qualitatively using a likert scale. The results showed that the Belerang Simpur tourist attraction consisted of three tourist attraction objects namely, Cecakhah Kenali waterfall, Belerang Simpur hot water, and natural panorama. Sapta pesona implementation based on the perception of tourists is divided into two categories, namely the category of both the elements of coolness and beauty, while the enough categories are found in the elements of security, order, cleanliness, friendliness, and memories. The development of attractions still needs to be improved by involving the role of the government and the management so that the management is more optimal.